The role of inter-religious dialogue in promoting Islamic education to the Europeans - Shehu, Fatmir (Zes Rokman Resources, 2018)
This study investigates the crucial role played by inter-religious dialogue in promoting Islamic education to the Europeans. Its goal is to provide a better understanding of Islam and its teachings through the channel of education in order to shift the views of Europeans on Islam and Muslims from hostility and enmity to mutual respect and friendliness. This paper starts with a brief introduction on the Europeans and their religious identity. Then, the main discussion focuses on: (1) what is inter-religious dialogue and Islamic education? (2) why inter-religious dialogue is an important means for the promotion of Islamic education to the Europeans (looking at the situation of European Muslims, their relationship with others, and contemporary issues)?, and (3) how inter-religious dialogue promotes Islamic education (discussing themes addressed in inter-religious dialogue activities, establishment of teaching modules, educational centers and institutions, where Islamic education is taught to the Europeans in a dialogue form)? Descriptive and analytical methods are employed by the researcher. This paper has achieved very useful findings that will serve as solid solutions for the proper understanding and interpretation of Islamic tenets through an appropriate Islamic education promoted by inter-religious dialogue.